Analysis of microtubule assembly kinetics using turbidimetry - Gaskin, Felicia (Methods in molecular biology (Clifton, N.J.), 2011)
Turbidity measurements are rapid and reliable methods to follow the effects of drugs, proteins, nucleotides, metals, and other factors on the assembly kinetics of tubulin into microtubules in vitro and have been in use since 1974. Improvements in spectrophotometers and software have resulted in the use of less protein, and more curves can be analyzed continuously and almost simultaneously.